2000
DOI: 10.1034/j.1600-079x.2001.280305.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a melatonin receptor within pancreatic islets of neonate rats: functional, autoradiographic, and molecular investigations

Abstract: In a recent perifusion investigation, we showed that the pineal secretory product melatonin reduces insulin secretion from isolated pancreatic islets of neonate rats stimulated with potassium chloride (KCl), glucose, and forskolin. This effect of melatonin was reproduced with doses ranging from 200 pmol/L to 5 μmol/L. Because it is generally accepted that melatonin exerts some of its biological effects through specific, high‐affinity pertussis‐toxin‐sensitive G‐protein‐coupled receptors, we blocked the putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
126
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(150 citation statements)
references
References 33 publications
17
126
1
5
Order By: Relevance
“…Insulin-stimulatory and -inhibitory effects Using rat INS-11 insulinoma cells it was determined that activation of inhibitory G-protein coupled (G i -coupled) MT1/MT2 receptors leads to significant reduction of cAMP synthesis, reduced activation of protein kinase A and, presumably, reduced insulin secretion [112]. Melatonin can also act through G i -coupled MT2 receptors in INS-1 cells to lower intracellular Ca 2+ levels [110,113], which is also predicted to reduce insulin secretion.…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 99%
“…Insulin-stimulatory and -inhibitory effects Using rat INS-11 insulinoma cells it was determined that activation of inhibitory G-protein coupled (G i -coupled) MT1/MT2 receptors leads to significant reduction of cAMP synthesis, reduced activation of protein kinase A and, presumably, reduced insulin secretion [112]. Melatonin can also act through G i -coupled MT2 receptors in INS-1 cells to lower intracellular Ca 2+ levels [110,113], which is also predicted to reduce insulin secretion.…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 99%
“…This indeed appears to be the case, as inferred from studies using the non-hydrolysable GTP analogue guanosine 5′-O-(3-thiotriphosphate) and the melatonin antagonist luzindole [51], both of which block the effects of melatonin on insulin secretion from neonatal rat islets. MTNR1A mRNA was subsequently demonstrated in INS-1 cells [52,53] and in rat [54,55] and human islets [55].…”
Section: Melatonin Receptors In Pancreatic Islets and Beta Cellsmentioning
confidence: 89%
“…Due to melatonin there is reduction in cAMP production in pancreatic islets and the rat insulinoma β-cell line INS1, as well as forskolin-stimulated insulin secretion from isolated pancreatic islets of neonate rats (33,46,47). The insulin and cAMP levels were stimulated by forskolin, adenylyl cyclase activator (48).…”
Section: Melatonin Signaling In Pancreatic β-Cellsmentioning
confidence: 99%
“…The insulin and cAMP levels were stimulated by forskolin, adenylyl cyclase activator (48). Previously it was found that receptor antagonists like luzindole completely reversed the cAMP-and insulin diminishing effects of melatonin (33). The Giα-protein-inhibitor pertussis toxin (PTX) abolished the effect of melatonin on the levels of cAMP and insulin as well (48).…”
Section: Melatonin Signaling In Pancreatic β-Cellsmentioning
confidence: 99%